2016
DOI: 10.1118/1.4946819
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Gaussian diffusion tensor imaging and non-Gaussian diffusion kurtosis imaging model-based estimates of diffusion tensor invariants in the human brain

Abstract: Model-dependent differences in the estimation of conventional indexes of MD/FA/MO/RD/AD can be well beyond commonly seen disease-related alterations. While estimating diffusion tensor-derived indexes using the DKI model may be advantageous in terms of mitigating b-value dependence of diffusivity estimates, such estimates should not be referred to as conventional DTI-derived indexes in order to avoid confusion in interpretation as well as multicenter comparisons. In order to assess the potential and advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 64 publications
0
17
1
Order By: Relevance
“…However, many of these interesting advances including both MRI acquisition and tractography approaches have not yet entered clinical routine. Nonetheless, recent technical innovations such as the use of optimized b -values and kurtosis tensor strategies (Marrale et al, 2015, Lanzafame et al, 2016) may further improve the future value of diffusion imaging in routine diagnostics. Furthermore, the improving processor power of modern computers will, in time, enable probabilistic DTI tractography to be fast enough for routine clinical use in preoperative tumour diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of these interesting advances including both MRI acquisition and tractography approaches have not yet entered clinical routine. Nonetheless, recent technical innovations such as the use of optimized b -values and kurtosis tensor strategies (Marrale et al, 2015, Lanzafame et al, 2016) may further improve the future value of diffusion imaging in routine diagnostics. Furthermore, the improving processor power of modern computers will, in time, enable probabilistic DTI tractography to be fast enough for routine clinical use in preoperative tumour diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, DKI quantifies the deviation from Gaussianity of the self-diffusion probability profile of water molecules in brain tissue. In a complex cytoarchitectonic environment such as white or grey matter, because such deviations are strongly influenced by the underlying microstructure, DKI indices are able to provide complementary information about microstructural alterations as compared with DTI alone [ 25 ]. In this context, a small number of previous studies investigated DKI alterations in glaucoma patients using a region-of interest (ROI)-based approach [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…An in-house implementation of the kurtosis model that integrates important constraints for robustness to noise (Groeschel et al, 2016 ) was found to improve the fit and the derived parameter maps. Since DT derived metrics from the DT model and the kurtosis model, however, are not directly comparable (Lanzafame et al, 2016 ), those parameters should be reported for both models. To further extend the comparison of DT model parameters obtained from CS-DSI and 3-shell HARDI, future work could convert CS-DSI and 3-shell HARDI data to corresponding single-shell HARDI data (Yeh and Verstynen, 2016 ).…”
Section: Discussionmentioning
confidence: 99%